Dynamics of Cosmic String and Domain Wall Cosmological Model with a Special Form of Deceleration Parameter - Mete, V. G.; Bayaskar, S. N.; Dhanagare, A. A.; Jalamkar, A. A. (Journal of Scientific Research, 2026)
In the present work, the Bianchi Type III spacetime is taken into account in the presence of a cosmic string and a domain wall within the framework of f(R,T) theory of gravitation. A specific form of the f(R,T), theory, namely f(R,T) = R + 2f(T), is taken into account in this work. The modified field equations for cosmic string and domain wall models are solved using a particular form of the deceleration parameter, and their physical behaviors are analyzed. In addition, the EoS parameter, jerk parameter, statefinder pair, and Om(z) diagnostic are utilized to analyze the evolutionary behavior of the Universe under the considered modified gravity model, indicating a quintessence-type nature of the cosmic expansion.This research offers significant insights into the anisotropic behaviour of the Universe and effectively describes the cosmic acceleration observed during late times. Our findings are then compared to recent observational data and are found to be in agreement with the ΛCDM model.